2021
DOI: 10.1002/advs.202100126
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Materials with Specific Wettability in Biomedical Engineering

Abstract: As a fundamental feature of solid surfaces, wettability is playing an increasingly important role in our daily life. Benefitting from the inspiration of biological paradigms and the development in manufacturing technology, numerous wettability materials with elaborately designed surface topology and chemical compositions have been fabricated. Based on these advances, wettability materials have found broad technological implications in various fields ranging from academy, industry, agriculture to biomedical eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 253 publications
(755 reference statements)
0
34
0
Order By: Relevance
“…Numerous conductive materials with micro/nanopatterns have been designed since patterns could endow them with enhanced wettability like hydrophobicity. [205,206] Taking Kim's work as an example, his group successfully constructed hydrophobic, stretchable and wrinkle-patterned PDMS films. [207] It has been demonstrated that the contact angle of the as-prepared PDMS was dependent on the size of the micro/nanostructures.…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…Numerous conductive materials with micro/nanopatterns have been designed since patterns could endow them with enhanced wettability like hydrophobicity. [205,206] Taking Kim's work as an example, his group successfully constructed hydrophobic, stretchable and wrinkle-patterned PDMS films. [207] It has been demonstrated that the contact angle of the as-prepared PDMS was dependent on the size of the micro/nanostructures.…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…As the surface wettability of the devices easily yet efficiently modulates their interaction with liquids, [ 64–66 ] the engineered surface wettability can prepare the devices for the target use in varying hydrated conditions (Figure 1, middle). The hydrophobic surface with water repellence can spontaneously and rapidly spread and roll off liquids, whereas the hydrophilic surface with excellent water affinity promotes surface wetting and liquid wicking.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58][59] Besides the (triboelectric) nanogenerators powered by the water/moisture or chemicals in sweat, the motion of raindrops and humidity difference can also provide renewable mechanical or chemical energies for energy harvesting to power sensors and devices. [60][61][62][63] As the surface wettability of the devices easily yet efficiently modulates their interaction with liquids, [64][65][66] the engineered surface wettability can prepare the devices for the target use in varying hydrated conditions (Figure 1, middle). The hydrophobic surface with water repellence can spontaneously and rapidly spread and roll off liquids, whereas the hydrophilic surface with excellent water affinity promotes surface wetting and liquid wicking.…”
mentioning
confidence: 99%
“…Superwettable surfaces, such as lotus leaf-inspired superhydrophobic surface, Namib Desert beetles-inspired patterned superwettable surface, and Nepenthes pitcher plant-inspired slippery surface, are commonly used for the development of novel superwettable biosensors. These bioinspired surfaces exert unique liquid-repellent performance with large contact angle, decreasing the contact area between the droplet and surface ( Dong et al, 2018 ; Sun et al, 2021 ). The remarkable wetting behavior brings several merits, such as remarkable evaporation-enrichment effect and new insights into visual biosensing.…”
Section: Introductionmentioning
confidence: 99%